Evaluation of potentially inappropriate medication utilization in elderly patients with cancer at outpatient oncology unit - OKUYAN, BETÜL; SANCAR, MESUT (SAGE PUBLICATIONS LTD, 2019)
Background The aim of the study was to evaluate potentially inappropriate medication use in elderly patients with cancer. Method This study was conducted at outpatient oncology clinic from December 2014 to March 2015 among elderly cancer patients. Screening Tool of Older Person's Prescriptions/Screening Tool to Alert doctors to Right Treatment criteria were used to identify potentially inappropriate medication in elderly patients. Results Among 114 cancer patients 55.26% of them were male and the mean age of them was 71.78 +/- 5.50 (years). The most common concurrent diseases were hypertension in 45 (39.47%) and diabetes in 26 (22.81%) patients. Polypharmacy (>= 5 medications) was seen in 94.73% of them. Eighteen patients (15.79%) utilized medications inappropriately according to Screening Tool of Older Person's Prescriptions criteria. Medication omissions were identified in 112 patients (98.25%) with Screening Tool to Alert doctors to Right Treatment criteria. Conclusions Clinical pharmacists could improve the current prescribing practices in elderly patients with cancer by assessing potentially inappropriate medications.
Keywords: Geriatrics; polypharmacy; clinical pharmacist; inappropriate medication; OLDER PERSONS PRESCRIPTIONS; ADVERSE DRUG-REACTIONS; STOPP/START CRITERIA; SCREENING TOOL; ALERT DOCTORS; POLYPHARMACY; PEOPLE; ADULTS; RISK; REHABILITATION